2015
DOI: 10.1111/ans.12967
|View full text |Cite
|
Sign up to set email alerts
|

Late two‐stage laparoscopic cholecystectomy is associated with an increased risk of major bile duct injury

Abstract: General surgeons should be aware of the increasing risk of major BDI with delaying TSLC and perform interval LC before week 16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A two-stage LC after 15 weeks following ERC/ES increases the rate of CTO three times (RR = 2.7, 95% CI: 1.4-5.5, P = 0.004) and major BDI 10-fold (RR = 10.2, 95% CI: 1.1-95.7, P = 0.043) [57]. Boerma et al compared the two-stage LC conducted within 6 weeks after ERC with that performed after 6 weeks and found that the latter was more technically demanding and associated with a threefold increase in the CTO rate (RR = 2.7, 95% CI: 1.3-3.4, P = 0.01) [58].…”
Section: Actual Problems Of Emergency Abdominal Surgerymentioning
confidence: 99%
“…A two-stage LC after 15 weeks following ERC/ES increases the rate of CTO three times (RR = 2.7, 95% CI: 1.4-5.5, P = 0.004) and major BDI 10-fold (RR = 10.2, 95% CI: 1.1-95.7, P = 0.043) [57]. Boerma et al compared the two-stage LC conducted within 6 weeks after ERC with that performed after 6 weeks and found that the latter was more technically demanding and associated with a threefold increase in the CTO rate (RR = 2.7, 95% CI: 1.3-3.4, P = 0.01) [58].…”
Section: Actual Problems Of Emergency Abdominal Surgerymentioning
confidence: 99%
“…Our conversion rate was lower than that in the previous literature. 31 Male gender, older age (>50 years), obese patients (body mass index > 30 kg/m 2 ), and case performed by low-volume surgeons had a higher likelihood to conversion in overall LC, [31][32][33] However, there was no single factor related to preoperative ERCP that would make LC more difficult except the number of ERCPs. 34,35 In our study, we found a higher age of patient and a larger proportion of difficult stone in the conversion group with statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cholelithiasis and choledocholithiasis require treatment of both of these entities. [13,15,16] Although there are several strategies for the treatment of combined choledochocystolithiasis, a commonly used strategy to treat patients is the two-stage management using preoperative ERCP with endoscopic sphincteroplasty and CBD stone removal followed by an interval LC. [3,9,17,18] With the widespread adoption of laparoscopy, single-stage treatments, such as CBD exploration and LERV techniques, have evolved with LC.…”
Section: Discussionmentioning
confidence: 99%
“…However, this time interval be-Şenocak et al Perioperative outcomes of the patients treated using LC after emergent ERCP for bile duct stones tween ERCP and LC ranges from days to months. [9,15,21] When viewed from this perspective, there is a paradoxical problem that needs to be resolved because a single-stage operation requires experience, and a two-stage operation has the risk of leading to recurrent attacks and increased complication rates if not carried out within the appropriate time frame. In this study, we analyzed the intraoperative and postoperative outcomes of the patients undergoing LC at three different time intervals after emergent ERCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation